2017
DOI: 10.1002/mma.4321
|View full text |Cite
|
Sign up to set email alerts
|

MHD Stokes flow and heat transfer in a lid‐driven square cavity under horizontal magnetic field

Abstract: This study considers the steady flow of a viscous, incompressible and electrically conducting fluid in a lid‐driven square cavity under the effect of a uniform horizontally applied magnetic field. The governing equations are obtained from the Navier‐Stokes equations including buoyancy and Lorentz force terms and the energy equation including Joule heating and viscous dissipation terms. These equations are solved iteratively in terms of velocity components, stream function, vorticity, temperature, and pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…They also employed the RBF approximation to MHD convection flow in different channels. 32,33 Geridonmez and Oztop 34 adopted RBF to MHD natural convection in a cavity subjected to cross partial magnetic field. They reported that the augmentation of Lorentz force decreases the convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…They also employed the RBF approximation to MHD convection flow in different channels. 32,33 Geridonmez and Oztop 34 adopted RBF to MHD natural convection in a cavity subjected to cross partial magnetic field. They reported that the augmentation of Lorentz force decreases the convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In literature review, it appears that heat transfer in natural convection power law non‐Newtonian fluid flow through vertical truncated wavy cone with the Tiwari and Das 22 nanofluid model has not yet been investigated. However, several overlapping studies in one or other way can be found in previous studies 23–41 . In order to fill the gap in literature, the thermally stratified boundary layer CNT–water nanofluid flow suspended by a vertical truncated cone is considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, several overlapping studies in one or other way can be found in previous studies. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] In order to fill the gap in literature, the thermally stratified boundary layer CNT-water nanofluid flow suspended by a vertical truncated cone is considered. Firstly, the system gives a nonsimilar solution; then it converts to a similar solution by using transformation to find its solution.…”
mentioning
confidence: 99%
“…They showed that temperature increases with increasing values of Eckert number. Gürbüz & Tezer-Sezgin (2018) studied the effect on viscous dissipation on MHD flow and heat transfer applying Stokes approximation (Re << 1) with small value of Grashof number 90. They found that both Stokes flow and isolines concentrate through the cold wall due to the viscous dissipation effect.…”
Section: Introductionmentioning
confidence: 99%